2018
DOI: 10.1111/conl.12571
|View full text |Cite
|
Sign up to set email alerts
|

Local human activities limit marine protection efficacy on Caribbean coral reefs

Abstract: Marine ecosystems globally have suffered habitat, biodiversity and function loss in response to human activity. Marine Protected Areas (MPAs) can limit extractive activities and enhance ecosystem resilience, but do not directly address external stressors. We surveyed 48 sites within seven MPAs and nearby unprotected areas to evaluate drivers of coral reef condition in the Mexican Caribbean. We found that local human activity limits protection effectiveness. Coral cover was positively related to protection char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 43 publications
6
53
2
Order By: Relevance
“…Nonetheless, Jackson et al (2014) established that in 1965 the coral cover of these areas was 34.1%, decreasing to 17.2% by 1999, showing a potentially important decrease in coral cover similar to the one documented in the Caribbean. In other areas such as Alacranes Reef, coral cover has been reported at 11.2% which, although lower than in the Veracruz Reef System, is still higher than some of the coral cover registered in Mexican Caribbean Reefs at <10% (Suchley and Álvarez-Filip, 2018), and very similar to the cover in Florida mentioned previously.…”
Section: Mexicosupporting
confidence: 69%
“…Nonetheless, Jackson et al (2014) established that in 1965 the coral cover of these areas was 34.1%, decreasing to 17.2% by 1999, showing a potentially important decrease in coral cover similar to the one documented in the Caribbean. In other areas such as Alacranes Reef, coral cover has been reported at 11.2% which, although lower than in the Veracruz Reef System, is still higher than some of the coral cover registered in Mexican Caribbean Reefs at <10% (Suchley and Álvarez-Filip, 2018), and very similar to the cover in Florida mentioned previously.…”
Section: Mexicosupporting
confidence: 69%
“…Likewise, MPA and fished sites in a case study from the Solomon Islands showed no differences in percent coral cover, likely due to excessive sedimentation at MPAs from destructive logging practices (Halpern et al, 2013). Analyses from Mexico and the Great Barrier Reef are more equivocal: MPAs can create resilience to short-term flood events (Olds et al, 2014), however, chronic or above-average flood exposure and human development ultimately outweigh MPA benefits, at times driving over 50% coral loss (Lamb et al, 2016;Wenger et al, 2016;Suchley and Alvarez-Filip, 2018). In sum, MPAs without forest conservation may be ineffective, and marrying vegetative land use with MPAs can improve crossecosystem outcomes.…”
Section: Surfacementioning
confidence: 99%
“…The Mexican Caribbean coast has experienced dramatic coastal development over the last decades. Over 10 million tourists visit the region annually and the local population has grown exponentially (Suchley & Alvarez-Filip, 2018). Consequently, coastal waters of the region have experienced eutrophication and increased sedimentation levels (Murray, 2007;Baker et al, 2013;Hernández-Terrones et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Eutrophication resulting from inadequate wastewater treatment has been previously identified as a major driver of declining reef condition in the region (e.g. Suchley & Alvarez-Filip, 2018). In addition and more recently, the Mexican Caribbean coast has regularly experienced a massive influx of drifting Sargassum that accumulates on the shores and rapidly decomposes, resulting in near-shore murky-brown waters that rapidly increases nutrient concentration in the water column and reduces light, oxygen and pH levels (van Tussenbroek et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation